Cultural Da'wah Harmony of Suran Punden Papringan Gede Tradition in Gunung Tugel Purwokerto - Saefulloh, Aris; Malik, Ahmed Abdul (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2024)
This study intends to identify and thoroughly examine the harmony achieved by cultural da'wah in the Punden Papringan Gede suran ritual in Gunung Tugel, Purwokerto. The local tradition of suran is a form of cultural knowledge that captures the community's identity and social ideals. The research data was gathered through interviews, document analysis, and observation. An anthropological method to qualitative data analysis is used in this study. The study's findings include: (1) the creation of new traditions through the blending of Islam and local culture; and (2) the harmony of cultural da'wah in the suran ritual of Punden Papringan Gede in Gunung Tugel Purwokerto, which is illustrated through a number of events like krigan, tahlilan, selawatan, orphan compensation, tumpengan, and puppets. These ethical values are part of the Suran Papringan Gede tradition on Gunung Tugel Purwokerto: gratitude, prayer requests, unity, relatives, solidarity, and a work ethic. According to the study's results, the cultural da'wah approach is one way to preserve the sustainability of regional customs, promote social cohesiveness, and enhance religious and cultural studies. Additionally, this research contributes in developing of an adaptable da'wah model which may be employed in various regions with related traditions.